Pronunciation Difficulties in English Learning: A Contrastive Analysis of MTs Students' Performance in East Kalimantan - Rostanti Toba; Anis Komariah (el Buhuth: Borneo Journal of Islamic Studies, 2026)
This study investigates the pronunciation difficulties encountered by MTs students in East Kalimantan when learning English as a foreign language. Using a comparative qualitative research method combining contrastive analysis between regional languages (as the first language or L1) and English (as a foreign language), this research examines the types of mispronunciations and underlying causal factors affecting 40 students from MTs Negeri 3 Paser and MTs Negeri 1 Penajam Paser Utara. Data collection involved students’ pronunciation recordings, in-depth interviews, and classroom observations. Findings reveal nine primary categories of pronunciation errors: (1) /gh/ endings pronounced as /f/, (2) silent /gh/ in word-medial positions, (3) silent /l/, (4) word-final /-d/, (5) word-initial /t/, (6) word-medial /ʒ/, (7) /ʃ/ substitution, (8) /θ/ substitution, and (9) word-final /-t/. Three main causal factors emerged: regional accent interference, phonological differences between the first language or L1/L2 (second language) and English, and unsupportive language environments. The study contributes to understanding multilingual students' English pronunciation challenges in Indonesian contexts and provides pedagogical implications for EFL (English as a Foreign Language) instruction.